Analysis of Law Number 20 of 2023 and the Role of Academic Manuscripts in Indonesian Law Formation - Budi Dharma, Widya Castrena; Syahuri, Taufiqurrohman; Thohari, Ahmad Ahsin (Research Horizon, 2025)
Article 43 paragraph (3) of Law Number 12 of 2021 requires that every Draft Bill (Rancangan Undang-Undang/RUU) submitted by the President, the People's Representative Council, or the Regional Representative Council must include an Academic Manuscript. This document contains a scientifically proven legal study outlining the necessity of regulating a problem and its resolution in the Draft Bill. The Academic Manuscript serves as a key reference during the legislative planning process. This study explores the role of the Academic Manuscript in law formation and analyzes the RUU on Amendments to Law Number 5 of 2014, focusing on its alignment with the Academic Manuscript. Using legal and empirical approaches, the research evaluates the application of norms under the Law on the Legislation Drafting, which mandates an Academic Manuscript for drafting laws. Law Number 20 of 2023 accommodates strategic issues highlighted in the Academic Manuscript. However, during the discussion process, the RUU underwent significant changes, with over 50% of its substance added. Despite these additions, the Academic Manuscript remained unchanged. Ultimately, the RUU led to the repeal of Law Number 5 of 2014 and its replacement with Law Number 20 of 2023, which redefines the regulations concerning the State Civil Apparatus.